STUDY ON THE CURRICULAR MATRIX OF THE UFSM BIOLOGICAL SCIENCES COURSE - Boton, Jaiane Moraes; Tolentino-Neto, Luiz Caldeira Brant de (Cadernos de Educação Tecnologia e Sociedade, 2019)
The teacher is an important actor in most people's lives. Considering the importance of this professional of his of the Training and the existing Teaching Knowledge that composes his practice, we aim, in this work, to investigate an initial training course of biology teachers. In order to do so, we analyzed the Pedagogical Project of the Biological Sciences Degree Program of the Federal University of Santa Maria, which was in force and was restructured in 2005. We focused on the following aspects: (i) how the Practice as a Component is developed Curricular (CCP; (ii) what semesters the CCP occurs in; (iii) how Supervised Curriculum Stages (ECS) are developed, and (iv) how the disciplines are distributed in relation to the Knowledge of Professional Training and Disciplinary Knowledge. Based on our analysis, we realize that the Course is documented in accordance with Resolution CNE / CP 2/2002, which regulates the duration and the compulsory workload for Basic Education Teachers, both in relation to the CCP and ECS. We also found that, even though there are more integrative orientations regarding disciplinary training and pedagogical training, there is still a prevalence of training focused on the specific subject area, with little space for pedagogical training. We hope that with the new legislation that will come into force in July 2019, the Biological Sciences Degree Program of UFSM will be restructured so as to give greater emphasis to the disciplines related to pedagogical training, thus giving place to the formation of professional identity of the undergraduate students.